Linear and nonlinear characteristics of the runoff response to regional climate factors in the Qira River basin, Xinjiang, Northwest China - Xue, Jie; Gui, Dongwei (PeerJ, 2015)
The inland river watersheds of arid Northwest China represent an example of how, in recent times, climatic warming has increased the complexity of Earth’s hydrological processes. In the present study, the linear and nonlinear characteristics of the runoff response to temperature and precipitation were investigated in the Qira River basin, located on the northern slope of the Kunlun Mountains. The results showed that average temperature on annual and seasonal scales has displayed a significantly increasing trend, but this has not been reflected in accumulated precipitation and runoff. Using path analysis, a positive link between precipitation and runoff was found both annually and in the summer season. Conversely, it was found that the impact of temperature on runoff has been negative since the 1960s, attributable to higher evaporation and infiltration in the Qira River basin. Over the past 50 years, abrupt changes in annual temperature, precipitation and runoff occurred in 1997, 1987 and 1995, respectively. Combined with analysis using the correlation dimension method, it was found that the temperature, precipitation and runoff, both annually and seasonally, possessed chaotic dynamic characteristics, implying that complex hydro-climatic processes must be introduced into other variables within models to describe the dynamics. In addition, as determined via rescaled range analysis, a consistent annual and seasonal decreasing trend in runoff under increasing temperature and precipitation conditions in the future should be taken into account. This work may provide a theoretical perspective that can be applied to the proper use and management of oasis water resources in the lower reaches of river basins like that of the Qira River.
Keywords: Climate change; Runoff response; Qira River basin; Linear characteristics; Nonlinear characteristics; Oasis; Xinjiang